Waterhyacinth: Florida’s Worst Floating Weed - Lyn A. Gettys (EDIS)
Waterhyacinth is one of the world’s worst aquatic weeds and is Florida’s most intensively managed floating plant. Dense mats formed by this species interfere with human uses of water bodies and disrupt ecosystems by preventing penetration of light and oxygen into the water column. This attractive, free-floating aquatic plant grows throughout the year in southern Florida but often dies back during the winter in the northern parts of the state. Waterhyacinth is cultivated as a water garden and pond plant, but cultivation, sale, and possession of this noxious weed is prohibited in Florida. This 5-page fact sheet was written by Lyn A. Gettys and published by the UF Department of Agronomy, September 2014.